Genome-wide identification of the pectin methylesterase inhibitor genes in Brassica napus and expression analysis of selected members - Wang, Duoduo; Jin, Shunda; Chen, Zhe; Shan, Yue; Li, Lei (Frontiers in Plant Science, 2022)
Pectin methylesterase inhibitors (PMEIs) modulate the status of pectin methylesterification by inhibiting the activity of pectin methylesterase (PME). Recent advances indicate PMEIs play an important role in regulating plant cell wall properties and defense responses. In this study, a genome-wide analysis of PMEI gene family in Brassica napus (B. napus) was conducted and the expression patterns of PMEI genes in response to Sclerotinia sclerotiorum (S. sclerotiorum) was investigated. A total of 190 PMEI proteins were identified from the genome of B. napus. Chromosomal location, gene structure and properties of the PMEI family were analyzed, and these features were compared with Arabidopsis thaliana (A. thaliana). A total of 123 syntenic ortholog pairs were detected from BnPMEI family by synteny analysis. Results showed the expansion of BnPMEI genes was likely predominately from whole-genome duplication (WGD) or segmental duplications. Multiple cis-elements related to plant growth and development, environmental stress responses, hormone responses were detected in the promoters of BnPMEI genes, implying they were regulated by both internal and external factors. Furthermore, expression analysis of transcriptome data combined with quantitative RT-PCR (qRT-PCR) validation identified several candidates that were strongly responsive to S. sclerotiorum infection. These BnPMEI genes are candidates for manipulation to breed novel and improved genotypes that are more resistant to sclerotinia stem rot (SSR). Extensive interactions were detected among 30 BnPMEI proteins, forming complex protein-protein interaction networks. Besides, 48 BnPMEIs showed interactions with other proteins including a range of cell wall structure-related enzymes. This study provides new insights into the evolution and function of PMEIs in B. napus and lays a foundation for breeding novel genotypes for crop improvement.